The economic feasibility of the accident insurance portfolio in the performance of insurance companies : an analytical study (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to use performance indicators and financial criteria in evaluating the economic feasibility of the company's insurance portfolios. In addition to identifying the strengths and weaknesses in portfolio's performance to enhance the strengths and address the weaknesses. This is consistent with research problem that dealt with the performance indicators, economic feasibility of company's portfolios and contributing to their improvement, reducing the financial and insurance risks associated with company's business. The research’ sample is represented by the Iraqi Insurance Company as it is one of the oldest financial institutions operating in the insurance sector. It has identified (5) insurance portfolios (marine, engineering, fire, accidents and supplementary cars). Data and information have been collected through the company's financial statements, profit centers, production plans, annual reports and annual statistics issued by the company for the time period (2016-2020). The research was based on the Insurance Business Law No. (10) of 2005, performance evaluation indicators issued by the FBSA. Which was represented by the administrative cost rate, production cost rate, compensation rate, retention rate, opportunity cost, net portfolio profit, profitability rate, growth rates, implementation rates and relative importance. As well as, adopting a set of descriptive statistics methods represented in the general average, standard deviation and percentages. The research concluded with a set of important results to identify weaknesses and strengths for the performance of insurance portfolios and assist the administration in making future decisions. The most notable is the lack of feasibility and benefit of issued reinsurance operations. As the total premiums waived by the company (the subject of research) exceeded the paid compensations and the company’s premium retention ratios do not match the paid compensations. Since the company incurred financial compensation more than its ability, this matter was reflected on the company's performance and the feasibility of its insurance portfolios.